Impact of Agricultural Mechanization on Agricultural Production, Income, and Mechanism: Evidence From Hubei Province, China - Peng, Jiquan; Zhao, Zihao; Liu, Dingning (Frontiers in Environmental Science, 2022)
Increasing agricultural operating income is not only an important step in improving agricul-tural work for farmers in the new era, but is also a powerful way to promote rural revitali-zation. To improve our understanding of the high-quality development of agriculture in China, the factors limiting agricultural income were analysed. Based on field survey data on farmers, this study analysed the influence of agricultural mechanization level on agricultur-al production and income by utilizing a sample-modified endogenous merging model and a threshold effect model. The level of mechanization has a significant positive impact on the cost, output value, income and yield of all types of crops. For every 1% increase in the level of mechanization, the yields of all crops, grain crops and cash crops increase by 1.2151%, 1.5941% and 0.4351%, respectively. Heterogeneity analysis shows that the level of mecha-nization has a certain threshold effect on income, with a greater effect occurring after the threshold. A test of action mechanism shows that the mechanization level can increase income via a factor intensification path and quality improvement path, with the partial mediation effects of the two paths being 28.8% and 27.4%, respectively. It is recommended to increase subsidies to purchase agricultural machinery, research and promote machinery suitable for cash crops, increase the level of socialized agricultural services, and improve the ability of farmers to apply novel agricultural machinery and tools so as to increase their operating profits.